PERSPEKTIF SOSIAL GURU TERHADAP LITERASI DIGITAL PADA PEMBELAJARAN BAHASA INGGRIS - I Putu Yoga Purandina (Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
This research is a research that investigates the social perception of teachers towards digital literacy in learning English in elementary schools. Then it was also explored about the obstacles in implementing digital literacy in learning English. Data acquisition and analysis was carried out qualitatively, using instruments in the form of a list of interview questions and also observation sheets. The results of this study are the teacher's social perception is very positive. The teachers have the same perspective where the teacher has a goal to make learning more varied, effective, easy, and fun. Then the teacher also has a goal to improve students' English skills along with increasing their digital literacy skills. The obstacles experienced by teachers are that there are still limited supporting infrastructure, such as PC or gadgets that are still lacking and students still do not have PC or gadgets that are controlled independently.